Efforts to Improve Student Learning Outcomes in Islamic Education Learning Using Audio Visual Media at SD Negeri 11 Trienggadeng - Nurmala; Rahmayani (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the effectiveness of using audio-visual media to improve learning outcomes of Islamic Religious Education in grade VI students of SDN 11 Trienggadeng. This study was conducted as a classroom action research consisting of two cycles, involving 30 students as research participants. The main objective of this study was to determine whether the integration of audio-visual learning materials would improve students' understanding of the topic